2MTF – VII. 2MASS Tully–Fisher survey final data release: distances for 2062 nearby spiral galaxies. Issue 2 (23rd May 2019) - Hong, Tao; Staveley-Smith, Lister; Masters, Karen L; Springob, Christopher M; Macri, Lucas M; Koribalski, Bärbel S; Jones, D Heath; Jarrett, Tom H; Crook, Aidan C; Howlett, Cullan; Qin, Fei
Abstract: We present the final distance measurements for the 2MASS Tully–Fisher (2MTF) survey. The final 2MTF catalogue contains 2062 nearby spiral galaxies in the CMB frame velocity range of 600 < cz < 10 000 km s −1 with a mean velocity of 4805 km s −1 . The main update in this release is the replacement of some archival HI data with newer ALFALFA data. Using the 2MTF template relation, we calculate the distances and peculiar velocities of all 2MTF galaxies. The mean uncertainties of the linear distance measurements are around 22 per cent in all three infrared bands. 2MTF measurements agree well with the distances from the Cosmicflows-3 compilation, which contains 1117 common galaxies, including 28 with SNIa distance measurements. Using distances estimated from the '3-bands combined' 2MTF sample and a χ 2 minimization method, we find best-fitting bulk flow amplitudes of 308 ± 26 km s − 1, 318 ± 29 km s −1, and 286 ± 25 km s −1 at depths of RI = 20, 30 and 40 h^-1 Mpc, respectively, which is consistent with the ΛCDM model and with previous 2MTF results with different estimation techniques and a preliminary catalogue.